Ontological And Axiological Foundations Of An Inclusive Society - Chorieva Madina Alievna (Emerging Frontiers Library for The American Journal of Engineering and Technology, 2025)
This article explores the ontological and axiological foundations of an inclusive society through the lens of contemporary philosophy and humanistic thought. The author analyzes inclusion not only as a social policy mechanism but as a form of being that embodies the essence of human coexistence, value recognition, and moral responsibility. The research argues that inclusivity is both an ontological condition of human being-in-the-world and an axiological imperative of modern civilization aimed at ensuring equality, dignity, and sustainable development.